Benthic biogeographic patterns in the southern Australian deep sea: Do historical museum records accord with recent systematic, but spatially limited, survey data?. Issue 23 (8th November 2018) - Tanner, Jason E.; Althaus, Franziska; Sorokin, Shirley J.; Williams, Alan
Abstract: Aim: To document biogeographic patterns in the deepwater benthic epifauna and demersal fishes of southern Australia, and determine whether museum records and systematic survey data provide matching results. Location: Southern Australian (32–44 o S) continental slope (200–3, 000 m deep). Taxon: Marine benthic fauna (Arthropoda, Bryozoa, Cnidaria, Echinodermata, Mollusca, Porifera, Sipuncula, and fishes). Methods: All available electronic records of fauna from the above taxa and ≥200 m depth off the southern Australian coastline, regardless of organism size, were collated from Australian museums and checked for geographic and taxonomic consistency. These records were then split into 40 geographic segments of roughly equal numbers, with each segment then treated as a sample in multivariate analyses of assemblage composition. Data from a recent (2015) systematic beam trawl survey along five north–south transects in the central Great Australian Bight were also included for comparison. Main conclusions: The systematic survey data grouped with the associated geographic segments despite differences in sampling technique (single gear compared to multiple gears), with subsequent differences in taxonomic biases, and the use of a 25 mm mesh, which would undersample some smaller organisms present in the museum data. Thus, the museum data and the survey data provided the same results for the central Great Australian Bight at the level of the whole assemblage. The main biogeographic break occurred off southeastern Tasmania, with a second substantial break occurring at around the border between New South Wales and Victoria. This indicates the potential for unused museum data to describe biogeographic patterns over regional spatial scales, especially in the deep sea where the expense of collecting new data is relatively high. Abstract : Historical data from Australian museum records are used to develop a deep‐sea biogeography for the southern Australian continental slope and indicate that the under‐sampled south‐facing coastline is distinct from the more heavily sampled eastern coastline. A recent systematic survey of the central Great Australian Bight on the south coast showed similar assemblage structure to that derived from the ad hoc collection of samples from close to 200 years represented in the museum collections.